The effects of competency-based education on midwifery students' knowledge, skills, and self-confidence for postpartum hemorrhage management - Masumah Hakimi; Masoomeh Kheirkhah; Jamileh Abolghasemi; Razia Hakimi (Kashan University of Medical Sciences, 2021)
Background: Hemorrhage is a leading cause of maternal death in the perinatal period. New teaching methods have been recommended for promoting midwives' competence in maternal care delivery. Objectives: This study was conducted to determine the effects of a competency-based education (CBE) program on midwifery students' knowledge, skills, and self-confidence for postpartum hemorrhage (PPH) management. Methods: This experimental study was conducted in 2018 on 86 third-, fourth-, and fifth-semester midwifery students recruited from the Faculty of Nursing and Midwifery of Iran University of Medical Sciences, Tehran, Iran. They were randomly allocated to either a control (n = 43) or an intervention group (n = 43). Participants in the control group received routine formal midwifery education, while their counterparts in the intervention group received CBE in addition to routine formal midwifery education. Participants' knowledge, skills, and self-confidence for PPH management were assessed at three time points, namely before, immediately after, and six weeks after the study intervention. Data were analyzed through performing the Chi-square and the independent-samples t-tests and the repeated measures analysis of variance. Results: There were no significant differences between the intervention and the control groups regarding the pretest mean scores of knowledge (4.87 ± 1.58 vs. 5.05 ± 2.07), skills (80.12 ± 5.72 vs. 82.30 ± 6.89), and self-confidence (7.05 ± 1.19 vs. 6.62 ± 1.47) (P > 0.05). In the intervention group, the mean scores of knowledge, skills, and self-confidence were significantly greater than the control group both at the first posttest (10.17 ± 1.31 vs. 5.20 ± 1.55, 301.15 ± 19.30 vs. 80.50 ± 5.12, and 9.47 ± 1.19 vs. 6.80 ± 0.91, respectively) and the second posttest (9.37 ± 2.21 vs. 5.32 ± 1.50, 299.67 ± 17.58 vs. 81.07 ± 5.69, and 9.72 ± 1.28 vs. 6.52 ± 1.44, respectively) (P < 0.05). Conclusion: CBE is effective in significantly improving midwifery students' knowledge, skills, and self-confidence for PPH management, and hence, it is recommended for promoting their competence.